Changes in tactile information during sports training in basketball players and swimmers - Kaluga, E.; Kostiukow, A.; Antosiak-Cyrak, K.; Rostkowska, E. (Journal of Kinesiology and Exercise Sciences, 2013)
Aim of the study. The aim of the study was to determine the changes in tactile information in two sport disciplines that train in different environments and in which different external stimuli affect the surface of the skin. Material and methods. Aesthesiometric measurements were carried out with 36 male basketball players, 32 female swimmers, and 32 women representing a control group, aged 19 to 20 years. In order to establish changes in tactile information taking place during sport training, measurements were taken 3 times (the first measurement was taken before the start of the training, the second measurement after 10 minutes, and the third measurement after 30 minutes of sport training) and on 3 measurement points of the dominant hand: on the pulp of the little finger, on the pulp of the index finger, and on the metacarpus on the inside of the hand between the thenar and hypothenar. A Touch-TestTM Sensory Evaluator (Semmes-Weinstein Monofilaments) aesthesiometer was used for the measurement. Nonparametric tests were used for the analysis of the results. Results. A gradual lowering of tactile sensitivity was noted in basketball players during training, and a gradual increase in tactile sensitivity was noted in swimmers during training. Conclusions. It was noted that during specialist sport training, changes in tactile